2013
DOI: 10.3390/ma6030897
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Transient Spectroscopy of Polymer/Fullerene Blends for Organic Photovoltaic Applications

Abstract: We measured the picoseconds (ps) transient dynamics of photoexcitations in blends of regio-regular poly(3-hexyl-thiophene) (RR-P3HT) (donors-D) and fullerene (PCBM) (acceptor-A) in an unprecedented broad spectral range of 0.25 to 2.5 eV. In D-A blends with maximum domain separation, such as RR-P3HT/PCBM, with (1.2:1) weight ratio having solar cell power conversion efficiency of ~4%, we found that although the intrachain excitons in the polymer domains decay within ~10 ps, no charge polarons are generated at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…Poly-methylmethacrylate (PMMA) as a kind of structural polymer, and regioregular-poly(3-hexylthiophene) (RR-P3HT) as a functional polymer with semiconducting property, were commonly used [ 9 , 14 , 15 , 16 , 17 , 18 ]. For instance, PMMA gratings could be used as diffractive components for optical devices or as a template for replicating other functional patterns [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-methylmethacrylate (PMMA) as a kind of structural polymer, and regioregular-poly(3-hexylthiophene) (RR-P3HT) as a functional polymer with semiconducting property, were commonly used [ 9 , 14 , 15 , 16 , 17 , 18 ]. For instance, PMMA gratings could be used as diffractive components for optical devices or as a template for replicating other functional patterns [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PMMA gratings could be used as diffractive components for optical devices or as a template for replicating other functional patterns [ 11 , 19 ]. The latter one, RR-P3HT, is widely used in organic solar cells and often used as an electron donor in the blend of P3HT: PCBM with PCBM as the acceptor [ 18 , 20 , 21 ]. Han et al have reported highly oriented nanofibrils of such semiconducting materials by blading deposition in a microfluidic dragging manner [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other approach entails separating the electron and hole in real space. An example is the extensively investigated polymer-fullerene blend system, in which ultrafast charge transfer from the polymer to the fullerene occurs after light excitation [13], leading to spatially separated electron and hole transport channels and very low carrier recombination rate (3 to 4 orders lower than the expected Langevin recombination rate) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to the synthesis of new polymers, molecular stacking in the active layer, and optimized device structures, evaluation methods of carrier dynamics in OPVs have been developed by many researchers [8] [9] [10] [11]. Several characterization techniques as carrier mobility of organic materials [12] [13], energy level at the interfaces [14] [15], and transient absorption spectroscopy [16] [17] have been investigated to understand carrier dynamics in the OPVs. Impedance spectroscopy is an important tool to discuss carrier dynamics including carrier mobility and density through the equivalent circuit of the device.…”
mentioning
confidence: 99%